PRESERVATION AND DEVELOPMENT OF THE ZAHIR MOSQUE AS A TOURISM HERITAGE SITE - Riski Sucahyo, Iqbal; Ismandi Bin Wasli, Mohamad; Mufidah Binti Mohd Noor Azam, Aini; Yasmin Binti Nor Madzalan, Norsyamimi; Binti Hassan, Nur’Ain; Puteri Dania Binti Nik Mat @ Nik Mohd Nazri, Nik; Haikal Bin Shahrul, Shahidin (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This study examines the preservation and development of the Zahir Mosque in Alor Setar, Kedah, as a cultural and religious heritage tourism destination. The novelty of this study lies in the integration of a holistic and participatory approach to understanding the mosque as a spiritual, educational, social, and tourism entity that are interconnected. A qualitative method was employed through field studies, semi-structured interviews, observations, and documentation. Data were analyzed using a six-phase thematic approach, supported by NVivo software. The findings show that the Zahir Mosque receives more than 50,000 visitors annually and contributes to a 20% growth in the local economy over the past five years. However, the high influx of tourists creates challenges such as disruptions to the solemnity of worship and the potential degradation of heritage values. This study recommends culturally based marketing strategies and sustainable preservation management involving local community participation. This research contributes to the cultural heritage literature by emphasizing the importance of mosque governance that balances religious, cultural, and economic values ABSTRAK Penelitian ini mengkaji pelestarian dan pengembangan Masjid Zahir di Alor Setar, Kedah, sebagai destinasi wisata warisan budaya dan religi. Kebaruan studi ini terletak pada integrasi pendekatan holistik dan partisipatif dalam memahami masjid sebagai entitas spiritual, edukatif, sosial, dan pariwisata yang saling terhubung. Penelitian ini menggunakan metode kualitatif melalui studi lapangan, wawancara semi-terstruktur, observasi, dan dokumentasi. Data dianalisis menggunakan pendekatan tematik berbasis enam tahap, dengan bantuan perangkat lunak NVivo. Hasil penelitian menunjukkan bahwa Masjid Zahir menerima lebih dari 50.000 pengunjung per tahun dan mendorong pertumbuhan ekonomi lokal sebesar 20% dalam lima tahun terakhir. Namun, tingginya arus wisata menimbulkan tantangan seperti gangguan kekhusyukan ibadah dan potensi degradasi nilai warisan. Studi ini merekomendasikan strategi pemasaran berbasis budaya dan manajemen pelestarian berkelanjutan yang melibatkan komunitas lokal. Penelitian ini berkontribusi pada literatur warisan budaya dengan menekankan pentingnya tata kelola masjid berbasis keseimbangan nilai religius, budaya, dan ekonomi.